Structure and Function: Planning a New Intensive Care Unit to Optimize Patient Care - Jozef Kesecioğlu (Türk Yoğun Bakim Derneği Dergisi)
To survey the recent medical literature reporting effects of intensive care unit (ICU) design on patients’ and family members’ well-being, safety and functionality. Features of ICU design linked to the needs of patients and their family are single-rooms, privacy, quiet surrounding, exposure to daylight, views of nature, prevention of infection, a family area and open visiting hours. Other features such as safety, working procedures, ergonomics and logistics have a direct impact on the patient care and the nursing and medical personnel. An organization structured on the needs of the patient and their family is mandatory in designing a new intensive care. The main aims in the design of a new department should be patient centered care, safety, functionality, innovation and a future-proof concept.